(untitled) (مجلة جامعة اللاذقية- سلسلة العلوم الاقتصادية والقانونية, 2020)
This research aims to identify the factors affecting the provisions of loan losses in the conventional private commercial banks operating in Syria, where the provisions contribute in the face of the risks that banks can be exposed to during the exercise of various activities. To achieve the goal of the research, annual data were collected from the financial statements of the 11 traditional private commercial banks operating in Syria, during the period from 2009 to 2009. The dependent variable that expresses loan loss provisions was measured by the ratio of loan loss provisions / total direct credit facilities, and the independent variables represented by the size of the bank, the ratio of Non-performing loans, the rate of loan growth was measured using the natural logarithm of total assets in the bank, loans Nonperforming / total direct credit facilities, annual change in loan growth, respectively. (1) For the purpose of analyzing the data, the random effects model was used to test the relationship between the dependent variable and the independent variables, and the data was analyzed using the Eviews 10 program. The results of the study showed that there is no effect of the rate of loan growth and the Syrian crisis in the provisions of loan losses, while the effect of the bank size, non-performing loans ratio, was positive in the provisions of loan losses. يهدف هذا البحث إلى التّعرف على العوامل المؤثّرة في مخصّصات خسائر القروض في المصارف التّجاريّة التّقليديّة الخاصّة العاملة في سورية، حيثُ تساهم المخصّصات في مواجهة المخاطر التي يمكن أن تتعرّض لها المصارف أثناء ممارستها للأنشطة المختلفة. لتحقيق هدف البحث تمّ جمع بيانات سنويّة من القوائم الماليّة للمصارف التّجاريّة التّقليديّة الخاصّة العاملة في سورية والبالغ عددها (11) مصرفاً وذلك خلال الفترة من عام 2017-2009. وقد تم قياس المتغير التّابع الّذي يعبّر عن مخصّصات خسائر القروض من خلال نسبة مخصّصات خسائر القروض / إجمالي التّسهيلات الائتمانيّة المباشرة، أمّا المتغيرات المستقلّة والمتمثلة في حجم المصرف، نسبة القروض المتعثرة، معدّل نمو القروض فقد تم قياسها باستخدام اللّوغاريتم الطّبيعي لإجمالي الأصول في المصرف، القروض المتعثّرة / إجمالي التّسهيلات الائتمانيّة المباشرة، التّغير السّنوي في نمو القروض على التوالي.([1]) وبغرض تحليل البيانات تمّ استخدام نموذج التّأثيرات العشوائيّة لاختبار العلاقة بين المتغير التّابع والمتغيرات المستقلّة، وتمّ تحليل البيانات بالاعتماد على برنامج EViews 10. أظهرت نتائج الدّراسة عدم وجود أثر لمعدّل نمو القروض والأزمة السّورية في مخصّصات خسائر القروض، بينما كان أثر حجم المصرف ونسبة القروض المتعثرة إيجابي في مخصّصات خسائر القروض. (1) يوجد العديد من محددات مخصّصات خسائر القروض منها ما هو داخلي مثل (حجم المصرف، نسبة القروض المتعثرة، معدل نمو القروض) ومنها ما هو خارجي مثل (معدل النمو في الناتج المحلي الإجمالي الحقيقي ومعدل التّضخم وسعر الصرف وغيرها من العوامل الخارجية). ولكن في هذه الدراسة سيتم الاقتصار على دراسة العوامل الداخلية فقط، بالإضافة إلى إدخال متغير وهمي هو الأزمة السّورية.